2001
DOI: 10.1067/mtc.2001.113023
|View full text |Cite
|
Sign up to set email alerts
|

Standard versus Hemodynamic Plus 19-mm St Jude Medical aortic valves

Abstract: Aortic valve replacement with 19-mm aortic prostheses in patients with a body surface area of less than 1.7 m(2) allows good results. Although Hemodynamic Plus models have better hemodynamic results, no significant difference was found in terms of clinical results and clinical hemolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Postoperatively, ATS heart valves showed similar profiles for LDH increase as demonstrated by Suedkamp et al and others [2,3]. No leakage or malfunction was observed in any patient and no other cause for LDH rise could be determined.…”
supporting
confidence: 82%
“…Postoperatively, ATS heart valves showed similar profiles for LDH increase as demonstrated by Suedkamp et al and others [2,3]. No leakage or malfunction was observed in any patient and no other cause for LDH rise could be determined.…”
supporting
confidence: 82%
“…8 -10,12,13 Milano et al 12 did not find a negative impact of P-PtM on long-term survival among patients with small SJM aortic prostheses, but only 8 patients had severe P-PtM in that study. Ismeno et al 11 found no survival advantage for the 19-mm HP valve over the 19-mm standard valve, despite a significantly lower mean gradient with the HP prosthesis. None of the patients in that study had an in vivo IEOA Ͻ0.9 cm 2 /m 2 , however.…”
Section: Impact Of P-ptm On Long-term Survivalmentioning
confidence: 99%
“…19,20 In a multivariate model, low effective orifice area was the unique predictor of a higher mean transprosthetic gradient. With the exception of homografts and probably stentless valves, all current prosthetic valve designs produce a measurable transprosthetic gradient that could potentially place persistent additional demands on the left ventricle and may hinder or delay the regression of left ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 99%